Temporal analysis and spatial distribution of acquired syphilis in the state of Mato Grosso, Brazil, 2010-2021: an ecological study - Susi Astolfo; Amanda Cristina de Souza Andrade; Ruth Terezinha Kehrig (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To analyze the temporal trend and the spatial distribution of acquired syphilis in Mato Grosso, Brazil, between 2010 and 2021. Methods: This was an ecological study using notifications of acquired syphilis held on the Notifiable Health Conditions Information System. Detection rates were calculated by health macro-region and three-year periods (2010-2012, 2013-2015, 2016-2018, 2019-2021). The jointpoint method was used to calculate annual percentage change (APC). Thematic maps of Bayesian rates were built and distribution was analyzed using Local Moran. Results: The detection rate increased from 16.2 per 100,000 inhabitants in the first three-year period (2010-2012) to 70.0 in the last three-year period (2019-2021). The Central-North macro-region had the highest rate in the last three years (94.3/100,000 inhab.), while the highest upward trend occurred in the Central-Northwest macro-region, from 2013 to 2018 (APC = 50.2; 95%CI 26.3;78.6). There was an increase in Bayesian rates in most municipalities. Conclusion: There was a trend towards an increase in acquired syphilis, especially in the last two three-year periods.